Notary Role in The Development of Tourism Industry: An Analysis of Business Licensing Policies - Alfian Anditya; I Made Pria Dharsana (Faculty of Law, Universitas Pekalongan, 2022)
The issuance of Law No. 11 of 2020 on Job Creation with its implementing regulations has marked a new era in the business licensing process in Indonesia since the introduction of the Online Single Submission system in 2018. These new licensing policies offer a more simplified licensing process and requirements that are designated to be applicable for every business sector in its establishment process, including the tourism sector as one of the nation’s biggest economic contributors. To obtain such benefits, tourism business players shall provide clear business information during the process of business registration in the licensing system and such information shall be provided under authentic corporate deeds that are made by a notary. This paper uses desk study research with a normative approach in analyzing the laws on licensing process, tourism sector, corporate matters, and notarial works that are prevails in Indonesia. This paper is not only elaborating on the business licensing process since the enactment of Law No. 11 of 2020 on Job Creation but it also analyses the relationship between the business licensing process and the notary’s responsibility as a public officer who is authorized by the law to draw authentic deeds. By understanding that relation, the correlation between the notary’s role and the development of the national tourism business, especially at the regional level could be identified. Thus, one of the efforts in developing tourism business across Indonesia is realized through notaries’ capability in understanding tourism business and its relevant legal knowledge together with an equal notary distribution in tourism destination areas.